Sandwich‐structured PPy‐TiO2/PVDF composite films with outstanding dielectric properties and energy density - Jinyue Qiu; Ling Weng; Xiaorui Zhang; Yu Su (IET Nanodielectrics, 2022)
Abstract Improving the energy storage density of dielectric capacitors has absorbed extensive attention for energy storage. However, a decrease in breakdown strength may be aroused after the addition of abundant fillers, it is necessary to design the composite film with a sandwich structure without the sacrifice of mechanical properties. The PPy‐TiO2/PVDF monolayer film and PVDF/PPy‐TiO2/PVDF sandwich‐structured composite films were successfully prepared via electrospinning and a hot‐press treatment. The experiment results show that the dielectric constant of the composite films can be enhanced effectively by adding PPy‐TiO2.When the filling amount is 30 wt%, the energy storage density of PVDF/PPy‐TiO2/PVDF sandwich‐structured composite films is outstanding before the breakdown strength, which is higher than that of the pure PVDF film. The energy storage density of PVDF/PPy‐TiO2/PVDF sandwich‐structured composite films could be achieved to 2.68 J/cm3 under the electric strength of 1700 kV/cm.